Titel prent: Achter het horretje : "Is het niet om te gieren? Die bende wil hetzelfde kiesrecht hebben als ik!" - Hahn, Albert
Titel prent: Achter het horretje : "Is het niet om te gieren? Die bende wil hetzelfde kiesrecht hebben als ik!".